2000
DOI: 10.1520/jfs14821j
|View full text |Cite
|
Sign up to set email alerts
|

Improved Method for Shooting Distance Determination. Part 2—Bullet Holes in Objects that Cannot be Processed in the Laboratory

Abstract: An improved method for firing distance determination on exhibits that cannot be processed in the laboratory such as cars, doors, windows, or furniture is described. The novel part of the method includes transfer of total nitrite (nitrite ions and smokeless powder residues) from the target to an adhesive lifter. After the transfer, vaporous lead and copper deposits around the bullet entrance hole are visualized on the target by sodium rhodizonate and rubeanic acid, respectively. The Modified Griess Test is carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…Glattstein et al [82] examined the feasibility of applying an adhesive lifter to the entrance bullet wound on human body surfaces to visualize total nitrite patterns, as was reported for clothing and other exhibits described above [68,75]. Figures 9 and 10 illustrate a case in which it was impossible to observe gunpowder residues around bullet entrance holes in the cadaver by visual or microscopic methods; the total nitrite pattern was, however, visualized on the adhesive lifter.…”
Section: The Human Body As a Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…Glattstein et al [82] examined the feasibility of applying an adhesive lifter to the entrance bullet wound on human body surfaces to visualize total nitrite patterns, as was reported for clothing and other exhibits described above [68,75]. Figures 9 and 10 illustrate a case in which it was impossible to observe gunpowder residues around bullet entrance holes in the cadaver by visual or microscopic methods; the total nitrite pattern was, however, visualized on the adhesive lifter.…”
Section: The Human Body As a Targetmentioning
confidence: 99%
“…Glattstein et al [75] examined the feasibility of the method developed for clothing [67], as described above, for additional materials such as galvanized steel, glass, plywood, and high-pressure laminated plastic sheets of melamine and phenolic materials (Formica). It was found that for all the target materials and shooting distances tested, the amounts and densities of the discharge residues detected visually (without any treatment) were considerably smaller than those obtained after chemical treatments.…”
Section: Exhibits That Cannot Be Processed In the Laboratorymentioning
confidence: 99%
“…However, in the literature on the chemical safety data [10], N-(1-naphthyl)-ethylenediamine dihydrochloride is not reported as a carcinogen. In fact, we are using this reagent with sulphanilamide routinely for "our" MGT [11,12,13,14]. MGT does not refer to one specific, defined test.…”
Section: Clothing Targetsmentioning
confidence: 99%
“…Glattstein et al [13] examined the feasibility of the method developed for clothing[12] (described above) for additional materials: galvanized steel, glass, plywood, and high-pressure laminated plastic sheets of melamine and phenolic materials (Formica). It was found for all tested target materials and shooting distances that the amounts and densities of the discharge residues detected visually (without any treatment) were considerably smaller than those obtained after chemical treatments.…”
Section: Exhibits That Cannot Be Processed In the Laboratorymentioning
confidence: 99%
See 1 more Smart Citation